FEATURES OF PERSONNEL MANAGEMENT AGRICULTURAL ENTERPRISES - Ніщенко, Т. М. (Scientific Progress & Innovations, 2014)
The article substantiates the need to consider socio-economic and educational qualification factors increased productivity for the effective use of personnel in enterprises of the agricultural sector. The system of personnel management as a complex mechanism between elements of which there is a close and indissoluble relationship. The basic structure of the components of human resource management in the agricultural enterprise. Particular attention is paid to providing effective professional impact of highly skilled workers.